Bring in quality in ESL teaching : bring in young adult novels in the classroom / Rahmah Mohd Rashid - Mohd Rashid, Rahmah (Institute of Quality and Knowledge Advancement (InQKA) and University Publication Centre (UPENA), 2007)
The paper examines issues in current teaching of English as a second language (ESL) in Malaysian classrooms and discusses how the ordinary chalk-board, grammar based, pedantically structural, or chunky communicative method might be intertwined with a more meaningful reading of the current young adult novels or literature. It also examines issues that the approach needs to consider relating to the current constraints of ESL teaching and its role in the national curriculum. The paper presents some rationale for this curricular innovation, and provides examples of how these books might be used in ESL classes.